2021
DOI: 10.1177/00131245211047207
|View full text |Cite
|
Sign up to set email alerts
|

“I Do Not Speak as Freely”: Gendered Views on Campus Carry at a Research University

Abstract: As campus carry policies are implemented at colleges and universities across the country, the concern for the safety of students, faculty members, and campus community members has heightened. In the state of Texas, broad sweeping campus carry policies were recently enacted by Texas State Legislature that allows individuals to conceal carry firearms within educational spaces on campus. Within these educational spaces, faculty members are often relied upon to deliver educational content without having their Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…First, students overwhelmingly reported no significant impact on their daily lives and their relationships on campus. This is significant as prior research focused on faculty has found campus carry policy to produce concrete changes in the behavior of these stakeholders (see Jones & Horan, 2019;Somers et al, 2017;Somers and Phelps, 2018;Somers, Gao, & Taylor, 2023). Second, the anxieties students expressed here regarding guns on campus in many ways existed in tension with the same students' reports that there was no impact on their behavior.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…First, students overwhelmingly reported no significant impact on their daily lives and their relationships on campus. This is significant as prior research focused on faculty has found campus carry policy to produce concrete changes in the behavior of these stakeholders (see Jones & Horan, 2019;Somers et al, 2017;Somers and Phelps, 2018;Somers, Gao, & Taylor, 2023). Second, the anxieties students expressed here regarding guns on campus in many ways existed in tension with the same students' reports that there was no impact on their behavior.…”
Section: Discussionmentioning
confidence: 80%
“…Some faculty reported attempts to move more of their courses online to increase safety, and faculty who are sexual minorities reported feeling considerably less safe (Somers et al, 2017). Somers, Gao, and Taylor (2023) combined survey and qualitative interview data of 226 faculty and staff members at a university in Texas to explore attitudes toward an existing campus carry policy. They found strong gender differences regarding faculty feelings of safety and position on the policy, with women faculty feeling less safe and more marginalized on campus.…”
Section: Perceived and Actual Impactmentioning
confidence: 99%
“…Though research on campus carry legislation has expanded over the years, how campus carry has impacted minoritized communities has remained limited (Ewing, 2017; Hassett et al, 2020; Somers & Valentine, 2021). Some empirical studies on campus carry policies have explored the perceptions of students (Bouffard et al, 2012; Brinker, 2008; Cavanaugh et al, 2012; Eaves et al, 2015; Jang et al, 2014; Kruis et al, 2020; Patten et al, 2013; Schildkraut et al, 2018; Thompson et al, 2013; Verrecchia & Hendrix, 2018); faculty (Bennett et al, 2012; Dahl et al, 2016; Drew, 2017; Jones & Horan, 2019; Somers et al, 2017; Thompson et al, 2012; Wolcott, 2017), and campus professionals and leaders such as advisors, campus police chiefs, and college presidents (Bartula & Bowen, 2015; Price et al, 2014, 2016; Somers et al, 2020; Thompson et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%